Application of Cognitive Behavior Therapy (CBT) in the Treatment of Patients with Substance Induced Psychotic Disorder (SIPD) - Rahmadini, Shabrina Fitri; Alfian, Ilham Nur (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Many people in Indonesia still use drugs with an estimated 4,8 million people from the entire population, and an increase of 0,15% compared to 2019. The type of drug that is often used is marijuana because it is relatively easy to obtain. Prolonged drug use can cause side effects, one of which is Substance Induce Psychotic Disorder (SIPD). Cognitive Behavior Therapy (CBT) is often given to treat psychosis so that the application of CBT to SIPD has a positive hypothesis. The aim of this study was to intervene in one of the patients with substance-induced psychotic disorder (SIPD). CBT was given to a 34-year-old patient of psychiatric hospital who suffered from SIPD due to prolonged consumption of marijuana. Researchers provide intervention in the form of Cognitive Behavior Therapy (CBT) with the aim of changing a weak belief system regarding the behavior of taking medication. The research method used in the research is qualitative case study research. CBT is effectively used as a therapeutic tool in shaping the subject’s negative thought patterns and behavior into more positive ones and can develop the subject’s potential. CBT can increase awareness of taking medication in SIPD patients. However, psychoeducation and additional interventions need to be provided, especially when the patient has returned home.Indonesia menghadapi tantangan besar dalam hal penggunaan narkoba. Diperkirakan 4,8 juta penduduk menggunakan narkoba, dan angka ini meningkat sebanyak 0,15% dibandingkan dengan tahun 2019. Jenis narkoba yang paling umum digunakan adalah ganja hal tersebut dikarenakan ganja relatif mudah didapatkan. Penggunaan narkoba dalam jangka panjang dapat menyebabkan berbagai efek samping, salah satunya yaitu gangguan Substance Induced Psychotic Disorder (SIPD). Terapi Cognitive Behavior Therapy (CBT) terbukti efektif dalam mengobati psikosis, sehingga penelitian ini bertujuan untuk menyelidiki penerapannya pada pasien Substance Induced Psychotic Disorder (SIPD). CBT diberikan pada pasien RSJ berusia 34 tahun yang mengidap SIPD akibat konsumsi ganja secara berkepanjangan. CBT secara khusus menargetkan keyakinan negative terkait kepatuhan terhadap pengobatan. Peneliti menggunakan pendekatan studi kasus kualitatif untuk menganalisis pengalaman pasien dengan CBT. CBT efektif dalam mengubah pola pikir dan perilaku negative pasien terkait dengan pengobatan. Dengan menumbuhkan pola pikir yang positif, CBT berkontribusi pada potensi pemulihan pasien. Penelitian ini juga menyoroti kebutuhan penting akan intervensi tambahan, seperti psikoedukasi, terutama setelah pasien keluar dari rumah sakit, untuk memastikan keberhasilan jangka panjang. Hasil dari penelitian ini menunjukkan bahwa Cognitive Behavior Therapy (CBT) efektif digunakan sebagai sarana terapi dalam pembentukan pola pikir dan perilaku subjek yang negatif menjadi lebih positif serta dapat mengembangkan potensi Subjek.